A 3D pitch and impact-angle constrained guidance scheme. (April 2019) - Varma, S Aditya; Kothari, Mangal
In this paper, a guidance scheme for achieving all the possible impact angles constraints for 3D engagements is proposed. For a simple and computationally efficient solution, our approach considers proportional navigation based impact-angle constrained guidance. However, the 3D proportional navigation law cannot be directly applied. This paper proposes a guidance strategy in which a 3D problem is divided into two consecutive 2D problems using a temporary target. The missile switches between the two planes using a temporary target. The paper begins with a simple approach and finally proposes a realistic solution. In all the scenarios considered, the guidance scheme achieves the desired impact angles. To further increase its effectiveness, the paper considers pitch constrained impact-angle law that drives the terminal angle of attack to zero. This ensures that the body axis of the missile will be aligned with its velocity vector at the time of impact. The effectiveness of the proposed guidance schemes are systematically verified through numerical simulations considering both kinematic and realistic models with first-order autopilot lag.